Volcanic Vortex Rings: Axial Dynamics, Acoustic Features, and Their Link to Vent Diameter and Supersonic Jet Flow. Issue 15 (28th July 2021) - Taddeucci, J.; Peña Fernández, J. J.; Cigala, V.; Kueppers, U.; Scarlato, P.; Del Bello, E.; Ricci, T.; Sesterhenn, J.; Panunzi, S.
Abstract: By injecting a mixture of gas and pyroclasts into the atmosphere, explosive volcanic eruptions frequently generate vortex rings, which are toroidal vortices formed by the jet's initial momentum. Here, we report high‐speed imaging and acoustic measurements of vortex rings sourcing from gas‐rich eruptive jets at Stromboli volcano (Italy). Volcanic vortex rings (VVRs) form at the vent together with an initial compression acoustic wave, VVRs maximum rise velocity being directly proportional to the amplitude and inversely proportional to the duration of the compression wave. The axial rise and acoustic signature of VVRs match well those predicted by recent fluid‐dynamic experiments. This good match allows using the high‐frequency (80–1, 000 Hz) component of the jet sound and the time‐dependent rise of VVRs to retrieve two key eruption parameters: the Mach number of the eruptive jets (<1.5) and vent diameter (∼0.7 m), respectively, the latter being confirmed independently by direct Uncrewed Aerial Vehicle observations. Plain Language Summary: Vortex rings are donut‐shaped vortices that form when a jet of fluid from a nozzle enters a fluid reservoir, as exemplified well by smoke rings (smoke blown from a mouth into air). Explosive volcanic eruptions produce vortex rings when a mixture of gas and particles erupts in the atmosphere from a circular vent. Here, we used slow‐motion videos and microphone recordings to study the vortex rings produced by the explosions of Stromboli volcano, in Italy. Applying recent fluid‐dynamic experimental findings to our novel observations, we were able to measure two important but elusive parameters of the explosions: the diameter of the vent and the ratio between the velocity of the gas‐particle mixture and the velocity of sound in the mixture. These results improve our capability to model dangerous eruptions and monitor volcanoes by their sound. Key Points: Volcanic vortex rings are formed by gas‐rich, jet‐forming Strombolian‐style explosions The explosion acoustic signals bear the signature of the vortex rings and reveal supersonic eruptive jets with Mach number up to 1.5 Vent diameter can be estimated from the time‐dependent rise of vortex rings at 0.7 m, in agreement with direct observation from Uncrewed Aerial Vehicle